Portofolio Hasil Karya Berbasis Website - Wafa, Shidqul; Airlangga, Primaadi (Lembaga Penelitian Pengabdian Masyarakat Universitas KH. A. Wahab Hasbullah, 2021)
Students who have completed their education and are ready to enter the job market need to know the importance of having a portfolio. because the company assesses the quality of applicants through a portfolio owned by job applicants. Some companies even recruit employees from portfolios regardless of educational background. While the problem of most students who are difficult to get a job is that students are not able to create their own portfolios properly. one solution that can be useful for students to support in terms of job search is a portfolio web application that can display the work of students. This application aims to provide a platform for students to be able to show off the work they create and can be a reference for a company to check the alignment of student skills for the work offered.